A new paradigm for understanding management technology: a research agenda for "technocologists". (4th August 2014) - Badawy, M. K.
This article focuses on developing a conceptual framework for understanding management as technology. A three–dimensional model design is introduced representing management core, enabling, and supporting technologies. The key characteristics of the new management paradigm are discussed. An application of the new paradigm to the area of management of technical professionals is presented. Some research directions for management of technology as an emerging discipline are also explored.